Pengaruh Karakteristik Pemerintah Daerah Dan Temuan Audit BPK RI Terhadap Akuntabilitas Kinerja Pemerintah Daerah - Nurdin, Fandy (Jurnal Ilmiah Mahasiswa FEB, 2014)
This research aims to examine the influence of the characteristic of local government (level of wealth, dependence level, and government expenditure) and audit finding to performance accountability of local government. Performance accountability is measured by scores on the evaluation of local government performance accountability. Population of this research is all the district/cities in Indonesia during 2012. Total this sample are 265 local government using stratified random sampling. Result of this research indicate that level of wealth significant positive influence on the performance accountability of local government, and for level of dependence significant negative on the performance accountability of local government. While government expenditure and audit findings had no significant influence to the performance accountability of local government in Indonesia. Keywords: characteristic of local government, audit finding, the performance accountability of local government, the performance accountability report of state apparatus (LAKIP), evaluation of local government performance accountability.